2014
DOI: 10.1007/s11682-014-9312-1
|View full text |Cite|
|
Sign up to set email alerts
|

A resting state functional magnetic resonance imaging study of concussion in collegiate athletes

Abstract: Sports-related concussions are currently diagnosed through multi-domain assessment by a medical professional and may utilize neurocognitive testing as an aide. However, these tests have only been able to detect differences in the days to week post-concussion. Here, we investigate a measure of brain function, namely resting state functional connectivity, which may detect residual brain differences in the weeks to months after concussion. Twenty-one student athletes (9 concussed within 6 months of enrollment; 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…Previous studies have variably found this pattern, and hyperconnectivity has been proposed to be involved in recovery and compensation for underlying white matter disruption. 4 , 30 33 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have variably found this pattern, and hyperconnectivity has been proposed to be involved in recovery and compensation for underlying white matter disruption. 4 , 30 33 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, our observation of similar time course of recovery for physiological effects and clinical symptoms following SRC runs contrary to recent work suggesting physiological effects extend beyond clinical recovery. For example, group differences in rs-FC have been reported in clinically recovered athletes after clearance for complete RTP (Churchill, Hutchison, Richards, et al, 2017), at approximately 10 days postinjury (Johnson et al, 2012), after 3 months postconcussion (Manning et al, 2017), and even within 6 months postconcussion (Czerniak et al, 2015). As highlighted in a recent systematic review, much of the prior work has included single postinjury visits and/or has included relatively small numbers of injured athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some recent studies have indicated a correlation between cognitive measures and functional [39,42,[48][49][50] or structural neuroimaging data [16,17,24,26,28], other studies have failed to do so [15,19,30].…”
Section: Correlations Of Dti Metrics and Resting State Data With Cognmentioning
confidence: 96%